Brazilin from Caesalpinia sappan inhibits viral infection against PRRSV via CD163ΔSRCR5 MARC-145 cells: an in silico and in vitro studies - Arjin, Chaiwat; Tateing, Suriya; Potapohn, Nuttha; Arunorat, Jirapat; Pringproa, Kidsadagon; Lumsangkul, Chompunut; Seel-audom, Mintra; Ruksiriwanich, Warintorn; Sringarm, Korawan (Scientific reports, 2022)
This research aimed to identify bioactive compounds from Caesalpinia sappan extract that function as novel porcine reproductive and respiratory syndrome virus (PRRSV) infection inhibitors by computational molecular screening. We obtained a set of small-molecule compounds predicted to target the scavenger receptor cysteine-rich domain 5 (SRCR5) of CD163. In addition, the functions of positive hits were assessed and verified utilizing an in vitro antiviral activity assay with PRRSV-infected MARC-145 cells. Combining molecular docking with the results of binding affinity and ligand conformation, it was found that brazilin had the highest binding energy with the SRCR5 receptor compared to catechin and epicatechin (− 5.8, − 5.5, and − 5.1 kcal/mol, respectively). In terms of molecular mechanics, the binding free energy between the SRCR5 receptor was − 15.71 kcal/mol based on the Poisson-Boltzmann surface area of brazilin. In addition, PRRSV infection in MARC-145 cells was significantly inhibited by brazilin compared to the control (virus titer, 4.10 vs. 9.25 TCID 50 /mL, respectively). Moreover, brazilin successfully limited the number of PRRSV RNA copies in MARC-145 cells as determined by RT-qPCR. By inhibiting the PRRSV-CD163 interaction with brazilin from Caesalpinia sappan , it may be possible to prevent PRRSV infection in pigs, as suggested by this research.